Penerapan Metode Naïve Bayes Untuk Rekomendasi Pemilihan Asisten Laboratorium Komputer Di Perguruan Tinggi - Derman Janner Lubis; Alfia Istiari Ningtiyas (Universitas Binaniaga Indonesia, 2022)
Binaniaga Indonesia University is one of the universities in the city of Bogor, just like other university in the learning process, computer laboratory assistants are often found whose job is to assist in providing appropriate directions to students who have difficulty during learning. Based on the results of interviews that have been conducted, there are indications that students who have been selected to become computer, laboratory assistants in the previous period, namely their performance is less than optimal, seen in daily life when assisting practicum courses in the computer laboratory, namely not providing the direction needed by practitioners who experience obstacles or difficulties, and also not optimal in terms of time while working in the computer laboratory. in this study, it can provide recommendations for selection of computer laboratory assistants to minimize errors in choosing computer laboratory assistants by applying the Naive Bayes method. The variables use is based on academic fields such as attendance, GPA (Gradual Achievement Index), the value of programming fundamentals courses, the value of programming language 1 or web systems and technology courses, and semester. The percentage of accuracy test results obtained by using the confussion matrix is the accuracy of 95.31%.